Antecipação de resultados futuros através da análise de multiplos no curto prazo - Andrade, Mário Geraldo Ferreira de (Universidade do Vale do Rio dos Sinos, 2013)
The dissertation main goal is to verify if the market has capacity of foreseeing high variations in financial indicators of the companies listed in BM&BOVESPA. They were chosen three indicators in the availability of given historical P/L price profit, P/Ebitda, price/ebitda and P/VPA price/valor patrimonial of the action. The comparison between given pasts in the period from 1994 to 2011 between given pasts tried to verify if the company profit tends to increase (decrease) when the indicator price/lucre (P/L) is above (below) of the waited, if the company profitability tends to increase (decrease) when the indicator market, company /value accounting (VM/VPA) is above (below) of the waited and to verify if Ebitda of the company tends to increase (decrease) when the indicator price/ebitda (P/Ebitda) is above (below) of the waited. Regarding the objective specific was to verify and indices financiers Price /lucre, Price/ebitda, and price/VPA at most high or low, in other words, outside the between average less and a deviation standard and average one more deviation standard, they tend to be adjust the average. For that was selected a company’s sample in each year of 1994 up to 2011 that presented quotations in ultimo year negotiation day that leave the indicator analyzed for one of the ends (high or low) were tried if multiple the average are adjusted and the market has capacity of anticipating future variations in the profit liquidate and the current price reflect correctly the company value, situation this according to the efficiency semi-strong of the Brazilian stock market. Already in the companies index relations in the inferior end, the market not hit capacity it presented efficient, however there is not a mistake systematic situation that could if characterize as an anomaly, thus, also in this case it accepts for hypothesis of efficiency semi-strong of the Brazilian stock market.
Keywords: Índices financeiros; Mercado acionário; Eficiência semi-forte; Financial indices; Stock market; Efficiency semi-strong; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis